Flow Boiling in Microgap Channels Experiment, Visualization and Analysis - Alam, Tamanna; Lee, Poh Seng.; Jin, Liwen; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Flow Boiling in Microgap Channels: Experiment, Visualization and Analysis presents an up-to-date summary of the details of the confined to unconfined flow boiling transition criteria, flow boiling heat transfer and pressure drop characteristics, instability characteristics, two phase flow pattern and flow regime map and the parametric study of microgap dimension. Advantages of flow boiling in microgaps over microchannels are also highlighted. The objective of this Brief is to obtain a better fundamental understanding of the flow boiling processes, compare the performance between microgap and conventional microchannel heat sinks, and evaluate the microgap heat sink for instabilities and hotspot mitigation.
Introduction -- Design and Operating Parameters -- Characteristics of Two-Phase Flow Boiling in Microgap Channel -- Comparison of Flow Boiling Characteristics between Microgap and Microchannel -- Optimization of Microgap Channel Dimension and Operating Condition -- Surface Roughness Effect on Microgap Channel -- Two-Phase Microgap Channel in Mitigating Flow Instabilities and Flow Reversal -- Two-Phase Microgap Channel Cooling Technology for Hotspots Mitigation -- Conclusions and Recommendations -- Appendix A: Uncertainty Analysis for Experimental Data -- Appendix B: Nomenclature -- Appendix C: Data Reduction.
Keywords: Engineering; Energy systems; Electric power production; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Engineering; Engineering Thermodynamics, Heat and Mass Transfer; Energy Technology; Energy Systems; Electronic books